Formulation and Evaluation of Metformin Hydrochloride Sublingual Film (Bangladesh Pharmaceutical Journal, 2025)
Metformin hydrochloride (HCl) fast-dissolving sublingual films were formulated to enhance bioavailability and minimize side effects through rapid onset of action and optimized drug-release and dissolution characteristics. Initially, the same formulation design with different ratios of metformin HCl (Drug), polymer A and plasticizer B was used to formulate nine batches of sublingual films utilizing solvent casting methods. The film formulations were evaluated based on morphological properties (color, clarity, flexibility and smoothness, trinocular microscopic image of film), physical properties (weight variation, thickness uniformity, folding endurance, surface pH, percentage of moisture loss, disintegration time, content uniformity), incompatibility (differential scanning calorimetry (DSC), Fourier-transform infrared (FTIR)), and drug release pattern. Compatibility studies deduced that there was minimal interaction between metformin HCl (drug) and the excipients (polymer, plasticizer etc), whereas trinocular microscopic images revealed the information about the surface of the film and the distribution of medication and polymer within the fast-dissolving film. Physical characterization of metformin HCl sublingual film was performed via morphological evaluations, weight variation, thickness uniformity, folding endurance, surface pH, percentage of moisture loss, in-vitro disintegration, in-vitro dissolution, drug content uniformity. The best formulation of films among all nine batches of film formulations was P1 with satisfactory outcome with respect to in-vitro dissolution 89.05% within 5 minutes, least disintegration time (28 sec), lowest thickness (221.4 ± 0.87) and optimum folding endurance (195 times). This study presents that the proposed metformin HCl film formulation can dramatically reduce dosage suffices to attain the effective drug concentration at the targeted region.Bangladesh Pharmaceutical Journal 28(2): 152-159, 2025 (July)